Global Research Trends on the Role of Chlorogenic Acid on Antidiabetic Mechanisms and Reproductive Hormone Regulation (2015-2025): A Bibliometric Analysis - Eko Naning Sofyanita; Ari Suwondo; Heri Nugroho; Achmad Zulfa Juniarto (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Chlorogenic acid (CGA) is a natural chemical discovered in a variety of plants that has been associated with numerous health benefits. Recent evidence suggests that CGA impacts reproductive hormone regulation, thus linking metabolic health and endocrine function. Understanding trends and gaps in research at this intersection is crucial. This study characterizes global research patterns, collaboration, and thematic evolution on CGA's antidiabetic activity and its influence on reproductive hormones through bibliometric analysis. Methods: Data were retrieved from the Scopus database using the keywords ("Chlorogenic Acid") AND ("Antidiabetic") AND ("Reproductive Hormone" OR "Testosterone" OR "LH" OR "FSH" OR "Estrogen" OR "Sperm" OR "Fertility") OR ("Reproductive Hormone" OR "Testosterone" OR "LH" OR "FSH" OR "Estrogen" OR "Sperm" OR "Fertility"). Publications from 2015 to 2025 were included. Bibliometric analysis was performed using VOSviewer and Biblioshiny to visualize co-authorship networks, keyword co-occurrence, publication trends, source dynamics, and thematic clusters. Results: A total of 162 relevant publications were identified, with a consistent increase observed from 2015 and a peak in 2024. Egypt, China, South Korea, and Saudi Arabia emerged as leading contributors, concentrating research in Asia and the Middle East. The primary journals were Molecules, Nutrients, and Frontiers in Pharmacology. Keyword mapping identified three principal clusters: phytochemical and antioxidant characterization, metabolic and antidiabetic mechanisms, and hormonal and molecular regulation. Thematic analysis revealed a shift from compound characterization to mechanistic and translational studies integrating metabolism and reproductive endocrinology. Conclusion: Global research increasingly highlights CGA as a bridge between metabolic and hormonal regulation. Our findings show a shift toward interdisciplinary, molecular investigations, but reveal significant gaps in clinical validation and formulation research. Unlocking CGA’s therapeutic potential in metabolic and reproductive health will depend on advanced multiomics, enhanced formulations, and greater global research partnerships.